Supply Chain Management Information System Model for Government Pension Fund Management in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aimed to develop and evaluate supply chain management information svstem model for government pension fund management in Thailand. The samples are ten experts in the field of information system and supply chain. The data is analysed by means and standardized deviations. The research result shows that the model consists of five elements namely main components, Suppliers, Government agency, Wholesalers, Customers. The assessment of model using Black-Box technique and the result shows the overall rating mean of 3.67 and standard deviation of 0.92, which means that the model is appropriate at the high level and can support an information system development.